MENYIKAPI PERUBAHAN POLA KONSUMSI MASYARAKAT PADA MASA PANDEMI COVID-19 - Ika Fitriyani; Rosyida Rachman; Novikadewi Sumbawati (FKIP Universitas Samawa, 2022)
The current pandemic condition affects people's activities online and offline. Despite economic limitations, citizen activities affect consumption and spending. Through surveys and online socialization, you will be able to provide information about people's consumption patterns and the costs incurred in meeting needs during the Covid-19 pandemic. The majority of residents prefer to increase the body's immunity by choosing consumption patterns with healthy food sources. This service activity aims to provide insight, description and information as well as motivation to the community about how people's consumption patterns are during the Covid-19 pandemic and before the Covid-19 pandemic. This activity is carried out offline and online through WhatsAap, Messenger and Instagram as well as via telephone. From this activity, we have obtained an overview and understanding of the importance of being wise during the Covid-19 pandemic for public consumption.